2013
DOI: 10.1007/s00268-013-2365-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Size Does Not Independently Affect Long‐Term Survival after Curative Resection of Solitary Hepatocellular Carcinoma Without Macroscopic Vascular Invasion

Abstract: Tumor size did not independently affect long-term survival and recurrence after curative resection of solitary HCC without macroscopic vascular invasion. Therefore, there is no size limit that precludes hepatic resection for solitary HCC, provided the tumor is resectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 58 publications
(55 reference statements)
3
40
1
Order By: Relevance
“…19 Other high-volume studies also supported that tumor size did not independently affect the long-term patient survival or tumor recurrence after curative resection of solitary HCC without vascular invasion. 8,20,21 Although there is no size cutoff for solitary HCC in the current AJCC TNM staging system, other HCC staging systems include tumor size. The BCLC system had size cutoffs at 2 and 5 cm, 9 but the cutoff at 5 cm was omitted at the BCLC/American Association for the Study of Liver Diseases (AASLD) guideline update in 2014 22 ; the Hong Kong Liver Cancer staging system has a cutoff at 5 cm 12 ; and the Japan Integrated Staging (JIS) Score includes a cutoff at 2 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Other high-volume studies also supported that tumor size did not independently affect the long-term patient survival or tumor recurrence after curative resection of solitary HCC without vascular invasion. 8,20,21 Although there is no size cutoff for solitary HCC in the current AJCC TNM staging system, other HCC staging systems include tumor size. The BCLC system had size cutoffs at 2 and 5 cm, 9 but the cutoff at 5 cm was omitted at the BCLC/American Association for the Study of Liver Diseases (AASLD) guideline update in 2014 22 ; the Hong Kong Liver Cancer staging system has a cutoff at 5 cm 12 ; and the Japan Integrated Staging (JIS) Score includes a cutoff at 2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, this tumor size-oriented concept was changed based on high-volume studies that showed that survival outcomes were independent of tumor size in patients who underwent resection of solitary HCCs without vascular invasion. 7,8 These results were reflected in the 6th and 7th versions of the American Joint Committee on Cancer (AJCC) Tumor-Node-Metastasis (TNM) staging system. It is generally suggested that there is no size limit that precludes hepatic resection of solitary HCC if the tumor is resectable.…”
Section: Introductionmentioning
confidence: 95%
“…When FDG-PET CT was not routinely available during the early phase of this study period, bone scan was performed instead. Liver function was assessed with indocyanine green retention rate at 15 min (ICG-R 15 ) and presence of portal hypertension (esophageal varix, noticeable collaterals, and splenomegaly with thrombocytopenia).…”
Section: Preoperative Evaluation and Surgical Proceduresmentioning
confidence: 99%
“…When liver cancer is discovered later or due to the influences of the biological features of tumors, tumors with larger diameters increase the possibility of vascular invasion, causing tumor cells to enter the bloodstream. Other studies have reported that tumor size does not correlate with survival rate but is associated with factors of poor prognosis such as vascular invasion, low histological differentiation, and multiple lesions (Zhang et al 2014). The percentage of patients with tumor diameters > 5 cm in the < 10 years of survival group was 71.6%, which was significantly higher than that in the ≥ 10 years of survival group ( P  < 0.01), while the 1-year, 3-year, 5-year, and 10-year cumulative survival rates of patients with tumor lesions ≤ 5 cm were higher than those of patients with tumor lesions > 5 cm (log-rank χ 2  = 39.835, P  < 0.01).…”
Section: Resultsmentioning
confidence: 97%
“…Different studies have proposed different AFP predictive values. Many studies use preoperative AFP > 400 µg/L as an independent risk factor of the prognosis after liver transplantation, and AFP > 400 µg/L has also been reported as a predictive factor of the prognosis of liver transplantation (Grąt et al 2014; Zhang et al 2014a, b; Hameed et al 2014). The incidence rate of AFP ≥ 400 µg/L among patients in the < 10 years of survival group was significantly higher than that in the ≥ 10 years of survival group ( P  = 0.002).…”
Section: Resultsmentioning
confidence: 99%